2019
DOI: 10.1371/journal.pntd.0007421
|View full text |Cite
|
Sign up to set email alerts
|

One hypervirulent clone, sequence type 283, accounts for a large proportion of invasive Streptococcus agalactiae isolated from humans and diseased tilapia in Southeast Asia

Abstract: Background In 2015, Singapore had the first and only reported foodborne outbreak of invasive disease caused by the group B Streptococcus (GBS; Streptococcus agalactiae ). Disease, predominantly septic arthritis and meningitis, was associated with sequence type (ST)283, acquired from eating raw farmed freshwater fish. Although GBS sepsis is well-described in neonates and older adults with co-morbidities, this outbreak affected non-pregnant and y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
82
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(89 citation statements)
references
References 76 publications
7
82
0
Order By: Relevance
“…The data presented showed that S. agalactiae was the more prevalent and geographically widespread aetiological agent, while S. iniae appeared to be confined to a specific area. While we acknowledge the limited sample sizes, these findings are in agreement with reports from neighbouring South‐East Asia (SEA) countries (Anshary, Kurniawan, Sriwulan, Ramil, & Baxa, 2014; Barkham et al., 2019; Jantrakajorn, Maisak, & Wongtavatchai, 2014; Kayansamruaj et al., 2019; Syuhada et al., 2020) and in China (Li et al., 2014; Su et al., 2019) where S. agalactiae is the primary streptococci species associated with fish disease. This observed prevalence of S. agalactiae over S. iniae is similar to reports worldwide, especially in the major tilapia‐producing regions in Asia and Latin America (Liu et al., 2016).…”
Section: Discussionsupporting
confidence: 91%
“…The data presented showed that S. agalactiae was the more prevalent and geographically widespread aetiological agent, while S. iniae appeared to be confined to a specific area. While we acknowledge the limited sample sizes, these findings are in agreement with reports from neighbouring South‐East Asia (SEA) countries (Anshary, Kurniawan, Sriwulan, Ramil, & Baxa, 2014; Barkham et al., 2019; Jantrakajorn, Maisak, & Wongtavatchai, 2014; Kayansamruaj et al., 2019; Syuhada et al., 2020) and in China (Li et al., 2014; Su et al., 2019) where S. agalactiae is the primary streptococci species associated with fish disease. This observed prevalence of S. agalactiae over S. iniae is similar to reports worldwide, especially in the major tilapia‐producing regions in Asia and Latin America (Liu et al., 2016).…”
Section: Discussionsupporting
confidence: 91%
“…This may include transfer of prophage content between GBS from different host species, in agreement with the detection of prophage types and integrase types across GBS from different host species in our dataset. We discovered a potential contribution of prophages to the emergence of hypervirulent ST283, which has recently been recognized as a major cause of adult invasive disease in Southeast Asia (Rajendram et al, 2016 ; Kalimuddin et al, 2017 ; Barkham et al, 2019 ). Contradicting the dogma that phage integrase genes are site-specific (Frost et al, 2005 ), the integrase at insertion site GBS7 (5' end of hylB ), was identical to the integrase at GBS1.…”
Section: Discussionmentioning
confidence: 95%
“…The label GBS Int 7 is not used because the site-specific integrase at insertion site GBS7 was identical to GBS Int 1 at insertion site GBS1 ( Figure 1 , Table 1 ). GBS Int 1 at site GBS7 was only observed in this location when the GBS1 site was occupied by a prophage and it was uniquely observed in ST283, the only known hypervirulent GBS in human adults (Barkham et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The GBS serotype Ⅲ ST283 was detected in three cage farms in the present study, suggesting the possibility of a genetically close relation. GBS serotype Ⅲ ST283 was widespread in South‐East Asia and emergence in Brazil, which has been proven to be associated with severe invasive disease in humans (Barkham et al, ; Leal et al, ). In 2015, GBS serotype Ⅲ ST283 was the causative agent of foodborne outbreaks in Singapore as the consumption of raw fish (Kalimuddin et al, ).…”
Section: Discussionmentioning
confidence: 99%